Effects of Humectant and Roasting on Physicochemical and Sensory Properties of Jerky Made from Spent Hen Meat - Supaluk Sorapukdee; Chanpen Uesakulrungrueng; Komkhae Pilasombut (My University, 2016)
This study was carried out to develop jerky product utilizing spent hen meat. Manipulation of water activity (aw) of semi-dried meat with the addition of humectants (glycerol and sorbitol at the concentration of 0, 10, and 15%) and roasting process were applied to enhance quality of jerky product. After spent hen meat was ground, formulated, reformed and then dried in convection oven at 85℃ for 2 h followed by 60℃ for 1 h, all jerky samples showed values of aw ≤0.85 with total aerobic bacteria, yeast and mold and Staphylococcus aureus counts were reduced to undetectable levels. Moreover, the results showed that the 15% glycerol added jerky showed superior quality, indicated by the lowest aw, low protein aggregation as evaluated by sorption isotherm and the lowest shear value as compared to sorbitol added and control samples (p<0.05). Regardless effect of humectant, roasting could improve the quality of the jerky via enhanced sensory attributes by increasing color, appearance, flavor and overall acceptability scores (p<0.05). Therefore, spent hen meat could be used as a potential raw material for jerky in which soft product texture obtained by the addition of glycerol and intense flavor resulted from roasting process after drying, leading to sensory acceptance.
Keywords: Roasting; Water activity; Meat and Animal Product Quality